Composition and optical property controlled in In 2 O 3 /W 2 N nanostructure composites by nitrogen plasma assisted in-situ thermal annealing - Saroni, A.; Alizadeh, M.; Rahman, S.A.; Dee, C.F.; Goh, B.T. (Elsevier, 2017)
In2O3/W2N nanostructure composites were grown by nitrogen plasma assisted in-situ thermal annealing at different hot-filament temperatures, Tf. The in-situ thermal annealing changes the as-grown In2O3 nanostructure to In2O3/W2N nanostructure composite with decreasing the grain size from 200 to 300 nm to ~ 100 nm. The optical spectroscopy results indicate that the optical energy gap of the nanostructure composites (3.7–2.7 eV) can be effectively tailored by monotonically increasing the W2N incorporation. The formation of W2N is attributed to the high energetic ion bombardment of N adatoms and incorporation of W adatoms. Furthermore, the effects of the filament temperature, Tf on the compositions in relation with the optical properties of the nanostructure composite are discussed.